Association between 23 drugs and inflammatory bowel disease: a two-sample Mendelian randomization study - He, Lei; Deng, Tuo; Huang, Yurong; Yang, Wangliu; Yang, Jie; Song, Gengqing (Frontiers in Medicine, 2024)
Background:Inflammatory bowel disease (IBD) is a group of diseases characterized by chronic and recurrent inflammation of the gastrointestinal tract. The etiology of IBD remains multifaceted and poorly understood, resulting in limited treatment causal associations with UC risk were found for β-receptor blockers {OR (95% CI) = 1.1893 [1.0823-1.3070], p = 0.0046}. A negative causal association with the risk of CD was found for immunosuppressants {OR (95% CI) = 0.6957 [0.5803-0.8341], p = 0.0023}. There was no statistically significant association between the remaining 19 drugs and IBD and subtypes.Conclusions:This MR study provides evidence suggesting that immunosuppressants have a mitigating effect on the risk of IBD and demonstrate consistent efficacy in subtypes of ulcerative colitis (UC) and Crohn's disease (CD). Additionally, diabetes medications show potential in reducing the risk of IBD, particularly in cases of UC, while β-blockers may elevate the risk of UC. Conversely, salicylic acid and its derivatives may increase the risk of IBD, although this effect is not consistently observed in the subtypes of the disease. These findings offer new insights into the prevention and management of IBD.